Dairy sheep and goats prefer the single components over the mixed ration - Berthel, Roxanne; Simmler, Michael; Dohme-Meier, Frigga; Keil, Nina (Frontiers in Veterinary Science, 2022)
Abstract Mixed-rations provide ruminants with a balanced diet by aiming to prevent selective feeding. However, this is a natural behavior of sheep and goats based on their dietary needs and the feed' nutritional properties. Therefore, the present study investigates non-lactating dairy sheep’s and goats’ acceptance of a mixed-ration when it is offered as choice next to its single components. Because all offered feeds were of comparable nutritional value, the animals were expected to not show a particular preference. Twelve pairs of sheep and goats each, were offered three different feeds simultaneously for five consecutive days. Two feeds consisted of a single component, hay (H) or grass-silage (G) of similar nutritional value. The third feed was a mixed-ration (M) including both single-feed components in a 50:50 dry-matter (DM) ratio. Feeds were offered ad libitum twice daily. The animals’ intake of each feed was recorded at six time points per day by weighing the leftovers. Feed preference was expressed as the natural logarithm of the ratio of the intake of the single component to the intake of M and analyzed using linear mixed-effects models. Additionally, the animals’ first choices after gaining access to the feeds were recorded at each weighing event and analyzed using an item-response-tree generalized mixed-effects model. The sheep’s average daily DM intake was 59(±11)% G, 26(±10)% H, and 15(±10)% M (mean ± standard deviation). Goats consumed an average of 56(±13)% G, 37(±12)% H, and 7(±6)% M daily. Both species preferred the single components to M in all observation periods. The proportions of the three feeds consumed differed throughout the day and between species. For both species, the estimated probability that an animal chooses a single component over M first was over 94% at all time points. These results show that, contrary to our expectations, non-lactating dairy sheep and goats prefer single components over a mixed ration of the same components and similar nutritional value. This might be caused by the animals seeking to diversify their feed throughout the day independent of apparent nutritional values and/or because sensory properties of the single components, indicating palatability, are relevantly reduced by mixing.